مشكلة الطاقة في الحوار العربي - الأوربي 1975- 1995 (Latakia University Journal - Economic and Legal Sciences Series, 2019)
انطلق الحوار العربي الأوربي منذ عام 1975,  واعترضت مسيرته مجموعة من المعوقات والقضايا الخلافية بين الطّرفين,  والتي من أهمّها ما يتعلق بإنتاج واستهلاك الطاقة,  وفي هذا البحث استعرضنا هذا الموضوع بتحليلٍ مفصّل وقدّمنا الاقتراحات المناسبة لتفعيل الحوار والتّغلّب على تلك المشكلة. وفي إطار هذا البحث قد تمّ معالجة أفكار أساسية تتعلّق بتطورات الحاجة الأوربية للطاقة لخدمة اقتصادياتها,  بالإضافة إلى السِّمات الرّئيسية لأسواق الطاقة العالمية والمفاوضات العربيّة الأوربية وتأثّرها بموضوع الطاقة,  إضافةً إلى عنوان هام هو الطاقة والبيئة, ومن تحليل تلك العناوين توصّلت الدراسة لصياغة مجموعة من المبادئ المقترحة لتكوين سياسات نفطية عربيّه وتقديم رؤية مستقبلية لطبيعة تلك السياسات وآفاقِها لخدمة عملية التّنمية الاقتصاديّة العربيّة وبما يتفق مع مصالح الشُّركاء في الحوار(المجموعة الأوربية).   Since it started in 1975,  the Arab-European dialogue has faced a number of problems,  including disagreements over a number of issues,  the most important of which relate to the production and consumption of energy. This study investigates this point of disagreement and seeks to settle it by providing appropriate suggestions that energize the dialogue. In the process,  the study examines the European need for energy to serve the European economy; the general characteristics of international energy markets; and the effect of Arab-European dialogue on them; as well as energy and the environment. Finally,  the study provides a number of suggestions aiming at the creation of a plan for future Arabic oil policies that serve both Arab economic interests and the interests of their European partners.